Effects of phonon dimensionality in the specific heat of multiwall carbon nanotubes at low temperatures - Jorge, G.A. (2009)
We have measured the specific heat at constant pressure, Cp, of three different samples of multiwall carbon nanotubes (MWNT). For all samples, Cp departs from a graphitic behavior at T < 120 K. Cp measurements show a temperature threshold from a linear regime for intermediate temperature to a higher-order power law for low temperatures. Moreover, it was found that this crossover only depends on the internal structure of the individual MWNT and not on the spatial order of the MWNT within a bundle. © 2009 IOP Publishing Ltd.